Checklist of the mites (Acari) of Türkiye. Third supplement - Erman, Orhan; Doğan, Salih; Ayyıldız, Nusret; Özkan, Muhlis (Salih DOĞAN, 2024)
As new species are described, taxonomic modifications or revisions are made and distributional data are increased, the checklists are frequently updated regularly. The present paper is a comprehensive supplementary document that aims to list the current species of mites (Acari) found in Türkiye. The species list is arranged alphabetically orders and includes the published records. According to the current information, among the 1241 taxa, 241 belong to the Mesostigmata, 19 to the Ixodida, 728 to the Trombidiformes and 253 to the Sarcoptiformes. This supplement might be a valuable resource for researchers and ecologists interested in understanding the biodiversity of mites in this region.
Keywords: Acarology; Akaroloji